2009
DOI: 10.1371/journal.pone.0005517
|View full text |Cite
|
Sign up to set email alerts
|

Attaching and Effacing Escherichia coli Downregulate DNA Mismatch Repair Protein In Vitro and Are Associated with Colorectal Adenocarcinomas in Humans

Abstract: BackgroundMucosa-associated Escherichia coli are frequently found in the colonic mucosa of patients with colorectal adenocarcinoma, but rarely in healthy controls. Chronic mucosal E. coli infection has therefore been linked to colonic tumourigenesis. E. coli strains carrying eae (encoding the bacterial adhesion protein intimin) attach intimately to the intestinal mucosa and are classed as attaching and effacing E. coli (AEEC). Enteropathogenic Escherichia coli (EPEC) are the most common form of AEEC identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
109
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 59 publications
5
109
1
2
Order By: Relevance
“…A cohort study showed that E. coli adherence to colonic mucosa may be linked to colorectal cancer [85]. Moreover, EPEC infection can activate PKCα, phosphorylate Bcl-2 and inhibit the transcription of MMR genes [86]. A/E E. coli infected intestinal epithelial cells by injecting toxic proteins, leading to DNA damage in host cells, and, together with the Toll-like receptor signaling pathway, the NF-κB pathway and other cell inflammatory pathways, accelerated the process of cancer [86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study showed that E. coli adherence to colonic mucosa may be linked to colorectal cancer [85]. Moreover, EPEC infection can activate PKCα, phosphorylate Bcl-2 and inhibit the transcription of MMR genes [86]. A/E E. coli infected intestinal epithelial cells by injecting toxic proteins, leading to DNA damage in host cells, and, together with the Toll-like receptor signaling pathway, the NF-κB pathway and other cell inflammatory pathways, accelerated the process of cancer [86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that CRC cells may be exposed to increased levels of LPS because of bacterial translocation (38) or systemic endogenous LPS without infections (39). It is suggested that LPS is an important component in the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of protumoral function by macrophages is directly influenced by tumor microenvironment. As several independent studies have reported high colonization by E. coli of adenomas and carcinomas in colon cancer patients, [15][16][17][18][19] we have analyzed the effect of such a microbial environmental factor on COX-2 expression in human macrophages. Phagocytic uptake of pathogens by macrophages results in the formation of vacuoles that rapidly evolve into bactericidal Figure 3 Intramacrophagic persistence of E. coli strains isolated from colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] In addition, our group and others have shown that colonic adenomas, carcinomas, and the mucosa of CRC patients are abnormally colonized by Escherichia coli belonging to the B2 phylogroup, with a high prevalence of E. coli producing a genotoxin, termed colibactin, encoded by the pks genomic island. [15][16][17][18][19][20] It has been recently demonstrated that cells that survive infection with colibactin-producing E. coli display hallmarks of cellular senescence accompanied with production of reactive oxygen species and secretion of pro-inflammatory cytokines, chemokines, and proteases, inducing bystander genotoxic and oncogenic effects. 21,22 Macrophages are one of the predominant components of murine and human tumor-infiltrating cells.…”
mentioning
confidence: 99%